Exceptional visuospatial imagery in schizophrenia; implications for madness and creativity - Benson, Taylor; Park, Sohee (Frontiers in Human Neuroscience, 2013)
Biographical and historical accounts suggest a link between scientific creativity and schizophrenia. Longitudinal studies of gifted children indicate that visuospatial imagery plays a pivotal role in exceptional achievements in science and mathematics. We asked whether visuospatial imagery is enhanced in individuals with schizophrenia (SZ). We compared SZ and matched healthy controls (HC) on five visuospatial tasks tapping parietal and frontoparietal functions. Two aspects of visuospatial transformation, spatial location and mental imagery manipulation were examined with Paper Folding Test and Jigsaw Puzzle Task, respectively. Visuospatial intelligence was assessed with Ravens Progressive Matrices, which is associated with frontoparietal network activity. Hemispatial inattention implicating parietal function was assessed with line bisection task. Mediated by prefrontal cortex, spatial delayed response task was used to index working memory maintenance, which was impaired in SZ compared to HC. In contrast, SZ showed intact visuospatial intelligence and transformation of location. Further, SZ performed significantly better than HC on jigsaw puzzle task indicating enhanced mental imagery manipulation. Spatial working memory maintenance and mental imagery manipulation were strongly associated in HC but dissociated in SZ. Thus, we observed enhanced mental imagery manipulation in SZ but the dissociation of mental imagery from working memory suggests a disrupted frontoparietal network. Finally, while HC showed the expected leftward pseudoneglect, SZ showed increased rightward line bisection bias implicating left hemispatial inattention and impaired right parietal control of spatial attention. The current results chart a unique profile of impaired, spared and enhanced parietal-mediated visuospatial functions implicating parietal abnormalities as a biobehavioral marker for SZ. We discuss these results in relation to creative cognition.